Benzathine Penicillin Prophylaxis in Children with Rheumatic Fever (RF)/ Rheumatic Heart Disease (RHD): A Study of Compliance - Radha G. Ghildiyal; Akanksha Gandhi; Milind S.Tullu (Al Ameen Medical College, 2010)
Aims and Objectives: To study the compliance of patients of Rheumatic fever (RF)/ Rheumatic heart disease (RHD) regarding secondary prophylaxis with injection benzathine penicillin. Materials and Methods: The study was conducted in the Pediatric Rheumatology Outpatients' Department (OPD) of a tertiary care teaching university affiliated hospital. Patients below 18 years of age diagnosed as Rheumatic fever/ Rheumatic heart disease following up in Pediatric Rheumatology OPD for at least 1 year for benzathine pencillin prophylaxis were included in the study. The patients diagnosed to have RF/ RHD were advised injection benzathine penicillin prophylaxis every 3 weeks. A proforma was devised for recording the clinical details of the patient- including demographic information, clinical details regarding RF/ RHD and rheumatic fever recurrences. The details of the benzathine penicillin prophylaxis taken by the patient were also recorded in the proforma. The reasons for non-compliance were noted and enlisted as per their frequency. Results: The study included 10 patients following up at the specialty clinic for rheumatic heart disease patients. We had 7 males and 3 females in the study. The average age was 9.7 yrs (6 years to 12 years). The average number of months of follow up for assessing the compliance was 20.7 months (12.6 months to 44 months). The average compliance (%) of the 10 patients was 89.60% (63.69% to 100%). Out of the 10 subjects, four had a recurrence of rheumatic fever manifesting in the form of congestive cardiac failure & carditis. Though most of the times the patients were not able to recall the reason for missing the dose, trip to one's native place was an important reason for missed doses besides forgetting the dates of the prophylaxis and doubts about need for the prophylaxis. Conclusions: Compliance of secondary prophylaxis with benzathine penicillin was about 90% in the present study. Frequent travel by patients to their native place was an important reason for missing the benzathine penicillin injections.